STATUS HUKUM HAK MILIK ATAS TANAH WARGA NEGARA ASING DENGAN MEMINJAM NAMA WARGA NEGARA INDONESIA - Astri Putri Aprilla; Iwan Permadi; Lutfi Efendi (Universitas Negeri Malang, 2018)
This article described the consideration of judges who won the foreign citizen in disputes over land ownership and the agreement validity to borrow the names of a foreign citizen in owner- ship of land rights under Article 1320 of the Criminal Code. This study method used normative legal methods with a legislative approach, a case approach, and a philosophical approach. The results of the analysis showed that the judge who won the foreign citizen as the defendant for the ownership of the land by using the name of the plaintiff based his decision on the inadequacy of the evidence or legally the claimant has the land rights. Agreements made by a foreign citizen and Indonesian citizens are null and void because they did not fulfil the legal requirements of an agreement, namely the existence of a lawful cause. Land that was the object of a lawsuit couldn’t be owned by a foreign citizen so that the land belongs to the state.DOI: http://dx.doi.org/10.17977/um019v3i12018p015